Developing an Evidence Base for Engagement and Impact in Higher Education Institutional e-Learning Projects - Carmichael, P.; Papaefthimiou, M-C; Alberts, P.; George, H.; Conole, G.; Brown, R. (Proceedings of the International Conference on Networked Learning, 2008)
This poster argues that an evidence-informed approach can be appropriate for ensuring accountability and validity of change initiatives in Higher Education (HE) in general and e-learning specifically, if recognition is made of the local context and the evidence-base gathered and used in situ. We describe how this model of evidence-informed practice is applied in relation to the HE Academy Pathfinder programme, a national "transformation initiative" in the UK. The goals of the programme are focused on exploiting and developing synergies to enhance and change practice where necessary. Four institutions (Cambridge, Reading, Brunel and London South Bank) are implementing an evidence-informed approach in different ways depending on their institutional context and culture. This poster draws upon collaborative activities of these institutions, focusing on the way in which they adapt common approaches to support their respective institutional change processes. It outlines the approaches adopted by each project and highlights the role of evidence in informing engagement with stakeholders and participants, and the development of practice in HE; ways of sharing models of evidence-informed practice in HE; and research approaches that can improve engagement with stakeholders and participants - while still generating high-quality research outcomes.